Campylobacter fetus subsp. venerealis adhesion to MDBK cells - Chiapparrone, María Laura (2014)
Members of the genus Campylobacter are recognized as causative agents of infectious diseases in humans and animals throughout the world. These bacteria are curved to spiral rods and have a single polar flagellum. Campylobacter fetus subsp. venerealis and Campylobacter fetus subsp. fetus are the causative agents of bovine genital campylobacteriosis, one of the most important venereal diseases in Argentina, which characteristically produces embryonic death and occasional abortion.